2015
DOI: 10.18052/www.scipress.com/ilshs.60.54
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between English Pronunciation Self-Concept and English Learning

Abstract: ABSTRACT. English pronunciation self-concept refers to self-evaluation of a person's English pronunciation proficiency which is shaped during the time spent for pronunciation learning (Gimson, 1980). The present paper aims at investigating the possible correlation between English pronunciation self-concept and English language learning. Furthermore, the relationship between global English self-concept and classroom anxieties are examined in the Iranian context. To this end, Xiuquan zhu's (2005) questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Another study supports the current one by Rahmawati (2010, as cited in Hamka, 2021), who found that self-concept correlates to students' speaking skills. Other researchers who conducted similar studies found a correlation between English selfconcept and English performance (Talebzadeh & Gholami, 2015;Wang, 2013;Tang et al, 2013;Liu, 2009). Furthermore, it is also evident in specific research that the English pronunciation selfconcept correlated significantly to the global English self-concept, which relatively leads to a high correlation to English performance (Talebzadeh & Gholami, 2015;Tang et al, 2013).…”
Section: Is There Any Significant Difference Between Students With Hi...mentioning
confidence: 76%
See 4 more Smart Citations
“…Another study supports the current one by Rahmawati (2010, as cited in Hamka, 2021), who found that self-concept correlates to students' speaking skills. Other researchers who conducted similar studies found a correlation between English selfconcept and English performance (Talebzadeh & Gholami, 2015;Wang, 2013;Tang et al, 2013;Liu, 2009). Furthermore, it is also evident in specific research that the English pronunciation selfconcept correlated significantly to the global English self-concept, which relatively leads to a high correlation to English performance (Talebzadeh & Gholami, 2015;Tang et al, 2013).…”
Section: Is There Any Significant Difference Between Students With Hi...mentioning
confidence: 76%
“…Their similar studies have concluded a high correlation between English self-concept and English achievement. Furthermore, it is also evident in specific research that the English pronunciation self-concept correlated significantly to the global English self-concept, which relatively leads to a high correlation to English performance (Talebzadeh & Gholami, 2015;Tang et al, 2013). However, the high positive results contradict Er's study (2012), which finds no correlation between foreign language selfconcept and reading comprehension test achievement.…”
Section: Literature Reviewmentioning
confidence: 85%
See 3 more Smart Citations